2009
DOI: 10.1007/s00726-009-0286-z
|View full text |Cite
|
Sign up to set email alerts
|

Testing biological activity of model Maillard reaction products: studies on gastric smooth muscle tissues

Abstract: Water-soluble Maillard reaction products obtained from five different model systems were investigated for their effects upon the mechanical activity of rat gastric smooth muscle. Most of the total Maillard reaction products applied at concentration of 1.5 mg/ml evoked contractions; among them the product obtained from arginine and glucose (Arg-Glc) produced the most powerful contractions. The product obtained from glycine and ascorbic acid (Gly-AsA) was the only one that brought about relaxation response. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Moreover, melanoidins did not significantly alter the latency of expulsion of a bead inserted 3 cm into the colorectum, suggesting that the motor agents (intrinsic and extrinsic innervation, smooth muscle, and ICCs) involved in the colonic propulsion at this level were not altered by dietary exposure to coffee silverskin-derived melanoidins and that these may have potential to be used as a functional food ingredient [178]. Interestingly, Argirova et al (2010) [185] showed that melanoidins act upon muscle tone and might facilitate Ca 2+ influx into the cells of isolated gastric muscle layers. Thus, these compounds might exert their pro-motility action not only through a fiber effect, but also through the direct activation of gastrointestinal smooth muscle cells, which needs to be confirmed to occur also using isolated intestinal muscle tissue.…”
Section: Maillard Reaction Products: Melanoidins and Acrylamidementioning
confidence: 98%
“…Moreover, melanoidins did not significantly alter the latency of expulsion of a bead inserted 3 cm into the colorectum, suggesting that the motor agents (intrinsic and extrinsic innervation, smooth muscle, and ICCs) involved in the colonic propulsion at this level were not altered by dietary exposure to coffee silverskin-derived melanoidins and that these may have potential to be used as a functional food ingredient [178]. Interestingly, Argirova et al (2010) [185] showed that melanoidins act upon muscle tone and might facilitate Ca 2+ influx into the cells of isolated gastric muscle layers. Thus, these compounds might exert their pro-motility action not only through a fiber effect, but also through the direct activation of gastrointestinal smooth muscle cells, which needs to be confirmed to occur also using isolated intestinal muscle tissue.…”
Section: Maillard Reaction Products: Melanoidins and Acrylamidementioning
confidence: 98%
“…Brown MRPs at low concentrations provoked concentration-dependent contraction, whereas brown MRPs at high concentrations induced muscle relaxation (Argirova, Stefanova, Krustev, & Turiiski, 2010).…”
Section: Other Biological Effectsmentioning
confidence: 99%
“… 37 In addition, several studies showed comparable effects of free and protein-linked CML in different cell lines. 10 , 11 As CML formation in the stomach has been reported to increase in the presence of catechols, 20 and several Maillard reaction products have been indicated to exert influence on the mechanical activity of the gastric smooth muscle, 17 we assessed the effect of CML on human parietal cells in culture, deriving from an adenocarcinoma of the stomach (HGT-1 cells). Furthermore, we have recently shown this cell line to be capable of serotonin biosynthesis and release upon stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Morioka et al , 16 positive Glycer-AGE immunostaining was observed in the stomachs of healthy rats. Argirova and colleagues 17 assessed the effects of water-soluble Maillard reaction products (MRPs), derived from different model systems, on the mechanical activity of the gastric smooth muscle from rats. Several of the compounds applied in this work led to contractions, among which the reaction products formed between glucose and arginine produced the strongest effect.…”
Section: Introductionmentioning
confidence: 99%